Vegetable glycerin e-cigarette aerosols cause airway inflammation and ion channel dysfunction - Kim, Michael D.; Chung, Samuel; Dennis, John S.; Yoshida, Makoto; Aguiar, Carolina; Aller, Sheyla P.; Mendes, Eliana S.; Schmid, Andreas; Sabater, Juan; Baumlin, Nathalie; Salathe, Matthias (Frontiers in Pharmacology, 2022)
Vegetable glycerin (VG) and propylene glycol (PG) serve as delivery vehicles for nicotine and flavorings in most e-cigarette (e-cig) liquids. Here, we investigated whether VG e-cig aerosols, in the absence of nicotine and flavors, impact parameters of mucociliary function in human volunteers, a large animal model (sheep), and air-liquid interface (ALI) cultures of primary human bronchial epithelial cells (HBECs). We found that VG-containing (VG or PG/VG), but not sole PG-containing, e-cig aerosols reduced the activity of nasal cystic fibrosis transmembrane conductance regulator (CFTR) in human volunteers who vaped for seven days. Markers of inflammation, including interleukin-6 (IL6), interleukin-8 (IL8) and matrix metalloproteinase-9 (MMP9) mRNAs, as well as MMP-9 activity and mucin 5AC (MUC5AC) expression levels, were also elevated in nasal samples from volunteers who vaped VG-containing e-liquids. In sheep, exposures to VG e-cig aerosols for five days increased mucus concentrations and MMP-9 activity in tracheal secretions and plasma levels of transforming growth factor-beta 1 (TGF-β1). In vitro exposure of HBECs to VG e-cig aerosols for five days decreased ciliary beating and increased mucus concentrations. VG e-cig aerosols also reduced CFTR function in HBECs, mechanistically by reducing membrane fluidity. Although VG e-cig aerosols did not increase MMP9 mRNA expression, expression levels of IL6, IL8, TGFB1, and MUC5AC mRNAs were significantly increased in HBECs after seven days of exposure. Thus, VG e-cig aerosols can potentially cause harm in the airway by inducing inflammation and ion channel dysfunction with consequent mucus hyperconcentration.